2012
DOI: 10.1007/s12298-012-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening of potato lines for drought tolerance

Abstract: Fresh water resources are limited and their use in agricultural production is expected to come under increasing constraints. Eighteen Syrian lines of potato (Solanum tuberosum L.) were screened for drought tolerance by measuring aerial and root growth in vitro. Drought stress was evaluated by adding 2, 4, 6, 8 and 10 % (w:v) of sorbitol to MurashigeSkoog medium and compared to 0 % for the control. Water potential of media ranged from −0.58 MPa to −2.5 MPa. Water-stress in culture adversely affected plant growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
50
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 28 publications
18
50
1
3
Order By: Relevance
“…The osmotic potential of the medium (Table S2, liquid medium) was comparable with values obtained by Gopal and Iwama () and Albiski et al. (), if the contribution of the agar was subtracted. The effect of agar on the osmotic potential of MS medium was analyzed before (Gopal et al.…”
Section: Discussionsupporting
confidence: 86%
“…The osmotic potential of the medium (Table S2, liquid medium) was comparable with values obtained by Gopal and Iwama () and Albiski et al. (), if the contribution of the agar was subtracted. The effect of agar on the osmotic potential of MS medium was analyzed before (Gopal et al.…”
Section: Discussionsupporting
confidence: 86%
“…Plants under water stress have been reported to show a decrease in leaf conductance (Obidiegwu et al, 2015), total area of leaves (Albiski et al, 2012), reduced plant chlorophyll content (Anithakumari et al, 2012), and the photosynthesis rate (Li et al, 2015). Loggini et al (1999), and Apel and Hirt (2004) reported that drought inhibits or slows down photosynthetic carbon fixation mainly through limiting the entry of CO 2 into the leaf or directly inhibiting metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Potato (Solanum tuberosum L.) is one of the most important vegetables in the world (Albiski et al, 2012). Potato is very sensitive to water-stress because of its shallower root system (Iwama and Yamaguchi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Also, under extreme water-stress conditions as induced by 0.4 M sorbitol, all genotypes had little shoot as well as root growth. Albiski et al (2012) reported that sorbitol inducing water stress in morphological parameters in potato. They mentioned that the drought induced by addition of sorbitol on MS medium led to decrease in the potato stem length, number of leaves and number of roots per plant according to potato genotypes and drought.…”
Section: Introductionmentioning
confidence: 99%